Effects of rescheduling on patient no-show behavior in outpatient clinics - LIU, Jiayi (Institutional Knowledge at Singapore Management University, 2019)
We study the effects of rescheduling on no-show behavior in an outpatient appointment system for both new and follow-up patients. Previous literature has primarily focused on new patients and investigated the role of waiting time on no-show probability. We offer a more nuanced understanding of this costly phenomenon. Using comprehensive clinical data, we demonstrate that for follow-up patients, their no-show probability decreases by 10.9 percentage points if their appointments were rescheduled at their own request, but increases by 6.2 percentage points if they were rescheduled by the clinic. New patients, in contrast, are more concerned about waiting time and less sensitive to who initiates rescheduling. Using data-driven simulation, we conduct counterfactual investigation of the impact of allowing active rescheduling on the performance of appointment systems. In particular, allowing the flexibility of active rescheduling can reduce the overall no-show rate and increase system utilization, but at a cost of increased wait time for new patients. If patients are able to reschedule at least one week in advance, new patients' wait time is largely reduced, while the no-show rate remains the same; this is equivalent to the effect of a 5% increase in the clinic's capacity.